Eradicating Helicobacter pylori and symptoms of non-ulcer dyspepsia. Issue 6812 (16th November 1991) - Patchett, S; Beattie, S; Leen, E; Keane, C; O'Morain, C
Abstract : OBJECTIVE--To examine the effect of eradication of Helicobacter pylori on symptoms of non-ulcer dyspepsia. DESIGN--Four week prospective study. SETTING--One hospital outpatient and endoscopy department. PATIENTS--90 adults with persistent symptoms typical of non-ulcer dyspepsia but no clinical or endoscopic evidence of other peptic, biliary, pancreatic, or malignant disease; all had histological and microbiological evidence of infection with H pylori. 83 patients completed the treatment regimen. INTERVENTION--Colloidal bismuth subcitrate 120 mg four times a day for four weeks (27 patients); metronidazole 400 mg and amoxycillin 500 mg each three times a day for one week (27); and bismuth subcitrate 120 mg four times a day for four weeks, metronidazole 400 mg three times a day for one week, plus amoxycillin 500 mg three times a day for the first week (29). MAIN OUTCOME MEASURES--Change in symptom scores determined with questionnaire; histological evidence of gastritis and microbiological evidence of presence of H pylori in biopsy specimens. RESULTS--Overall, H pylori was eradicated in 41 (49%) patients. Although gastritis scores improved significantly in only patients in whom H pylori had been eradicated (from 1.56 to 0.61, p less than 0.01 v from 1.83 to 1.07, p = 0.52) mean symptom scores after treatment were similar in patients in whom H pylori had or had not been eradicated (3.0 v 2.3, NS). Similarly the mean symptom score improved whether or not gastritis improved (2.8 v 3.1 respectively, p = 0.72). The observations were similar for treatment groups analysed individually. CONCLUSION--Antral infection with the organism does not seem to have an important aetiological role in non-ulcer dyspepsia short term.